PENGEMBANGAN PARIWISATA MENUJU INDONESIA EMAS 2045 DAN PERAN PRINSIP AUGUSTE COMTE - Dina Mayasari Soeswoyo (Bogor Hospitality Journal, 2024)
The development of Indonesian tourism formally began when there was a determination of tourism as an independent science, which then developed until it was finally able to become the leading of sector. However, this development is still not optimal, so a vision and mission for future tourism development is created which is summarized in the book of Indonesia Emas 2045. The purpose of this study is to describe the principle role of the great philosopher Auguste Comte in the development of Indonesian tourism. This research is a library study from various previous scientific papers, books, performance reports and notes, which are analyzed qualitatively. The results of this study describe the role of Auguste Comte's principles in the development of Indonesian tourism from the perspective of ontology, epistemology and axiology. Keywords: Auguste Comte; Tourism development; Indonesia Emas; Tourism phylosophy